PENGARUH PENAMBAHAN ALKANOLAMIDA TURUNAN MINYAK KELAPA SAWIT TERHADAP SIFAT-SIFAT UJI TARIK VULKANISAT KARET ALAM BERPENGISI SILIKA - Darwis Syarifuddin Hutapea, Harry Laksana Tampubolon, Indra Surya (Jurnal Teknik Kimia USU, 2012)
By using semi-efficient sulfur accelerated vulcanization sistem, an investigation about function of the alkanolamide as additive material on silica filled natural  rubber was carried out. Alkanolamide was made by reacted between refined bleaching deodorized palm stearin with diethanolamine. Alkanolamide was added  to the natural rubber compound silica filled, which is resulted vulcanizate natural  rubber filled compound and occurring increasing of tensile strength, modulusand crosslinkdensity  up to 5 phr. If was added  more 5 phr, so  reduction of the tensile strength modulus and crosslink density.Keywords : Alkanolamide,Tensile Strength, Crosslink Density, Natural Rubber Vulcanizate